The Effect of Chronic Administration of Amphetamine-Type Stimulants on Oxidative Stress and Inflammation in Wistar Rats - Vita Camellia; Fasihah Irfani Fitri; Muhammad Ichwan; Dina Keumala Sari; Elmeida Effendy; Aldy Safruddin Rambe; Syafruddin Ilyas; Juliandi; Alfi Khatib; Mustafa Mahmud Amin; Muhammad Rusda (مجلة بغداد للعلوم)
This study aims to determine the effect of chronic administration of amphetamine-type stimulants at varying doses on inflammation and oxidative stress in Wistar rats. They were given methylphenidate and divided into 4 treatment groups. Furthermore, simple random grouping was carried out to divide the samples into 5 groups, each consisting of 9 rats. These groups included rats given only distilled water as the controls, as well as those given methylphenidate at doses of 10 mg/kg BW, 20 mg/kg BW, and 40 mg/kg BW for 4 weeks as the experimental groups. Statistical analysis was then performed using GraphPad Prism to compare the effects of oxidative stress, systemic inflammation, BDNF, and spatial memory of the Wistar rats. Chronic administration of stimulants led to a significant decrease in glutathione peroxidase levels as well as an increase in the release of IL-6 and tumor necrosis factor-α compared to the control group. Based on the results, the pathways involved in cognitive impairment, which were related to the use of amphetamine-type stimulants played a role in addressing the detrimental effect of substance abuse and their comorbidities